2020
DOI: 10.5194/isprs-archives-xliii-b4-2020-329-2020
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning Helps Slam: Learning to Build Maps

Abstract: Abstract. In this research, we investigate the use of Reinforcement Learning (RL) for an effective and robust solution for exploring unknown and indoor environments and reconstructing their maps. We benefit from a Simultaneous Localization and Mapping (SLAM) algorithm for real-time robot localization and mapping. Three different reward functions are compared and tested in different environments with growing complexity. The performances of the three different RL-based path planners are assessed not only on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…DRL planner contribution: Without predictor, mapping using PPO is equal and even better comparing to the frontierbased method, in 10 to 50 percents (for completed episodes), while the difference is higher for the well ordered dataset D 1 and lower for D 2 . These results seams to improve the reported results in [8] [9] [10] where RL was nearly optimal. Yet, the predictor's contribution is the primary and DRL's contribution is the secondary.…”
Section: Simulation Results and Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…DRL planner contribution: Without predictor, mapping using PPO is equal and even better comparing to the frontierbased method, in 10 to 50 percents (for completed episodes), while the difference is higher for the well ordered dataset D 1 and lower for D 2 . These results seams to improve the reported results in [8] [9] [10] where RL was nearly optimal. Yet, the predictor's contribution is the primary and DRL's contribution is the secondary.…”
Section: Simulation Results and Analysissupporting
confidence: 78%
“…Two conceptually different reward functions can be used: one that yields all the reward at the end of an episode (sparse) or one that provides a series of temporal rewards. The authors of [10] compared these two options and concluded that the second is preferable. This is not surprising, since rewarding momentary partial exposures encourages the agent to expose more cells, hence speeding up the learning process.…”
Section: B Reward Functionmentioning
confidence: 99%
“…By integrating the techniques such as computer vision, deep learning, and reinforcement learning, UAV-based SLAM can achieve more advanced and complex tasks, such as autonomous navigation, object manipulation, and so forth. Several studies (Botteghi et al, 2020;Wen, Zhao, et al, 2020) with SLAM (Aslan et al, 2022;Cheein et al, 2011;Krul et al, 2021).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…We note that, for such sensor-based path planning and/or target detection problems, machine learning-based methods have been on the agenda recently. In particular, reinforcement learning (RL) approach appears to be gaining popularity as an adaptive optimization methodology [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%